Crisis prevention and the Coronavirus pandemic as a global and total risk of our time - Radoica Luburić (Journal of Central Banking Theory and Practice, 2021)
The Coronavirus pandemic, as a global and total risk of our time, has imposed the need for a more complete and comprehensive review of existing approaches to crisis prevention and preventive management in general. This crisis also pointed to some shortcomings in quality management, risk management and change management, which had not been removed in a timely and adequate manner in more stable conditions in order to function better in crisis situations. Accordingly, the structure of this paper was conceived, which, in addition to an introduction and concluding remarks, has five short, but thematically complete, units. In the first part, preventive management is seen as a paradigm of the successful management of problems, incidents and crises. In the second and third parts, the influence of the principles of quality management and the principles of risk management on the prevention of a crisis, as well as their cooperation, effectiveness and synergistic effects are discussed. The fourth part analyses the key processes of change and conflict management in terms of crisis prevention. In the fifth part, an effective, complete and comprehensive crisis prevention model based on quality management, risk management and change management is created, with the primary goal of achieving sustained success in all business conditions. Bearing in mind that the processes and conse-quences of the Coronavirus pandemic have still not been completed or become clear, the concluding remarks identify certain messages and lessons that could have been learned in its initial stages.
Keywords: M10; M19; M54; 330; Preventive Management; Crisis; Quality Management Principles; Risk Management Principles; Change Management; a Model of Crisis Prevention; Coronavirus Pandemic; Coronavirus; Krisenmanagement; Risikomanagement; Qualitätsmanagement; Organisatorischer Wandel